Biophysical analysis of the 200m front crawl swimming: a case study - Figueiredo, P.; Sousa, A.; Gonçalves, P.; Suzana, P.; Susana, S.; Vilas-Boas, J. P.; Fernandes, R. J. (Biomechanics and Medicine in Swimming XI, 2010)
INTRODUCTION: Propulsive and drag forces acting on the swimmer`s body are major performance determinants, being affected by technique, motor organisation and control. The muscular activity, as the energy expenditure, are also swimming influencing parameters. It was studied the 200m maximal front crawl of an elite Olympic swimmer, analysing the intracyclic velocity variation of the centre of mass, arm coordination, energy expenditure and neuromuscular activity. METHODS: A male swimmer (21 yrs, 71kg and 180cm), national record holder, swam 200m for the assessment of the intracyclic velocity variation (IVV) in x, y and z axes (2 surface and 4 underwater cameras, Sony® DCR-HC42E, digitised with APASystem and determined through the coefficient of variation of the velocity of the centre of mass), arm coordination (Index of Coordination - IdC - Chollet et al., 2000, using the digitised model), oxygen uptake (K4b2) and neuromuscular activity (surface electromyography - EMG) of the flexor carpi radialis, biceps brachii, triceps brachii, pectoralis major, upper trapezius, rectus femoris, biceps femoris and tibialis anterior muscles. A spectral index (cf. Dimitrov et al., 2006) was calculated for one stroke cycle for each 25m. Afterwards, swimmer performed 50, 100 and 150m at the 200m pace for blood lactate kinetics analysis (Lactate Pro), which allowed the assessment of the total energy expenditure (Ë). Linear regression was assessed on muscle EMG parameters (p < 0.05). RESULTS: It was observed a decay of velocity, stroke length and stroke rate through the 200m, with a slightly increase of this last parameter in the last lap. IVVx maintained stable and larger magnitudes of IVV were found for y and z than in x axis. IdC kept in the catch-up mode, increasing in the last 100m. Ë increased in the 1st 50m, resulting from an exponential increase of the VO2 kinetics, reaching the VO2 peak in the 2nd 50m. In 4th 50m, the glycolitic contribution was found to be higher, which lead to high values of Ë. It was also found a significant increase of the fatigue indices for the most studied muscles. DISCUSSION: It was observed an interaction of important coordinative, biomechanical, electrophysiological, and bioenergetical performance influencing parameters. Changes in some factors imply other changes or offer the stability needed for a better performance.